2023
DOI: 10.1186/s12951-023-02052-5
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-conjugated isotretinoin for controlled transdermal drug delivery

Tianqi Zhao,
Mingwei Zhou,
Ronghui Wu
et al.

Abstract: Background In the present study, we aimed to develop a novel isotretinoin delivery model for treating skin diseases, revealing its potential advantages in drug delivery and targeted therapy. Using a self-assembly strategy, we grafted a dendrimer, based on a well-defined branched structure for nanomedical devices, with a well-defined nanoarchitecture, yielding spherical, highly homogeneous molecules with multiple surface functionalities. Accordingly, a self-assembled dendrimer-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The IMQ-induced psoriatic mouse model was established to evaluate the therapeutic efficacy of the formulation [ 32 ]. Based on the above results, 10% DES (4:6)-RM was selected as the topical delivery carrier of TA, namely TA@DES-RM (containing 0.1% TA, w/w).…”
Section: Methodsmentioning
confidence: 99%
“…The IMQ-induced psoriatic mouse model was established to evaluate the therapeutic efficacy of the formulation [ 32 ]. Based on the above results, 10% DES (4:6)-RM was selected as the topical delivery carrier of TA, namely TA@DES-RM (containing 0.1% TA, w/w).…”
Section: Methodsmentioning
confidence: 99%
“…These advantageous release characteristics could reduce the teratogenic side effects of isotretinoin, facilitating effective skin penetration. In vitro and in vivo studies showed that dendrimers improved the penetration rate of the isotretinoin to the lower layers of the skin, thus targeting lesions more effectively [ 154 ]. Table 9 summarizes the above-mentioned dendrimers.…”
Section: Current Nanotechnology-based Approaches For the Topical Trea...mentioning
confidence: 99%
“…Dendrimers have attracted significant attention in various fields, including drug delivery, due to their unique properties, such as a uniform size, well-defined architecture, and the ability to encapsulate drugs or other molecules. Dendrimers have hydrophobic and hydrophilic exteriors, similar to lipid bilayer membranes, enabling them to encapsulate different drugs [ 65 ]. We should distinguish between poly-(amidoamine) (PAMAM) dendrimers, showing their drawback of leading to biodegradation products—“acrylates”, and the peptide dendrimers, which show a lower toxicity, as they degrade to harmless amino acids.…”
Section: Liposomes and Related Vesicles As Nanocarriers For Anti-acne...mentioning
confidence: 99%
“…A self-assembled dendrimer-conjugated system was developed to achieve the enhanced percutaneous penetration of isotretinoin [ 65 ]. The authors reported that the isotretinoin-loaded dendrimers showed a remarkable controlled release, characterized by a slow release in normal tissues but accelerated release in tissues with low pH, such as sites of inflammation.…”
Section: Topical Retinoidsmentioning
confidence: 99%